Soundscape Ecology and Posthumanist Music Practice: An Approach Towards Ecological Healing - Xiahong Qiao (Journal of Dharma, 2025)
The world is gradually awakening to the severity of contemporary ecological crises. Among these, noise pollution has emerged as a silent yet devastating threat, damaging the environment since the dawn of industrial modernity. The replacement of human labour with heavy machinery, the expansion of large-scale technological installations, and the transition from agricultural ecosystems to highly industrialized landscapes have introduced a new and troubling dimension to ecological degradation. These developments have not only inflicted profound harm on natural ecosystems but have also alienated humanity from the very sounds of nature that once nurtured calmness, relaxation, healing, and an intimate sense of connection with the natural world. Today, people have become more accustomed to the noise of factories and vehicles than to the harmonious acoustic environment of nature. The pursuit of technological advancement and economic gain—whether through deforestation, industrial emissions damaging the ozone layer, or the relentless acceleration of scientific intervention—continues to exacerbate ecological decline. This study proposes soundscape ecology as a crucial corrective lens for addressing the current ecological crisis. It argues that the lyrical heritage of musicality carries significant potential for ecological restoration, and it highlights the need for posthuman music practices that centre the well-being of the environment. In doing so, it calls for a renewed music-literary consciousness that rekindles humanity’s connection with nature